Building Ḍ at Magdala revisited in the light of public fountain architecture in the late-hellenistic east - Bonnie, Rick (Israel exploration journal, 2012)
The small columnar Building D1 discovered at Magdala in the early 1970s was first identified by the excavators as a mini-synagogue. Although Ehud Netzer has convincingly opposed this view, arguing that the building functioned as a fountain house, some scholars challenge Netzer's identification, most notably on the basis of a doubtful comparison with a supposedly canonic type of Roman nymphaeum. Consequently, alternative interpretations for the function of this building, such as a synagogue or a latrine, continue to appear in the literature. This paper argues that the building has not been compared to the right category of public fountains. Indeed, Magdala's Building D1 presents strong similarities with contemporary examples of late-Hellenistic fountain architecture in Asia Minor and fits perfectly within the context of the long-term evolution of the so-called stoa-shaped fountain houses. The function of Building D1 as a fountain house, as argued by Netzer, seems very likely, particularly on the basis of comparative data from the city of Sagalassos (south-west Turkey).